PENGARUH WCT, DER TERHADAP ROE PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA YANG GO PUBLIK - Hisar, Roy; Suharna, Jaka (Jurnal Ekonomi : Journal of Economic, 2020)
This study aims to determine the effect of Working Capital Turnover (WCT), Debt Equity Ratio (DER) simultaneously on Return On Equity (ROE). The research samples used in this study were 65 companies, namely the Basic Industry and Chemical companies which were listed on the Indonesia Stock Exchange during 2013-2017. The data analysis used was ANOVA and Partial Regression test. The results showed that WCT and DER had a significantly positive effect on ROE from the results of research on the Basic and Chemical Industry companies, so that accounting information has a value of relevance to investment decisions. Working Capital Turnover Variable, partially has a significant negative effect on Return On Equity. Debt Equity Ratio variable partially has a significant negative effect on Return On Equity.Â Keywords : Working Capital Turnover, Debt Equity Ratio, Return On Equity